2010
DOI: 10.1017/s0022215110001453
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node central necrosis on computed tomography as predictor of extracapsular spread in metastatic head and neck squamous cell carcinoma: pilot study

Abstract: Objective-This study aimed (1) to investigate the relationship between the presence of lymph node central necrosis, viewed on pre-operative computed tomography imaging, and the occurrence of histopathologically determined metastatic lymph node extracapsular spread and (2) to determine whether a larger scale study would be valuable. Conclusions-Lymph node central necrosis viewed on pre-operative computed tomography scans is a useful indicator of metastatic lymph node extracapsular spread, with a sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Cervical nodal metastasis is very common and has a substantial effect on prognosis in patients with HNSCC. Zoumalan et al (13) and Randall et al (14) reported that CNN that was visible at preoperative CT was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with HNSCC, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% (15)(16)(17)(18)(19). These previous studies indirectly suggested that CNN may also be a negative prognostic factor in patients with HNSCC, including NPC; the results of our current study confirm this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical nodal metastasis is very common and has a substantial effect on prognosis in patients with HNSCC. Zoumalan et al (13) and Randall et al (14) reported that CNN that was visible at preoperative CT was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with HNSCC, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% (15)(16)(17)(18)(19). These previous studies indirectly suggested that CNN may also be a negative prognostic factor in patients with HNSCC, including NPC; the results of our current study confirm this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that rates of distant metastasis were higher in npc patients with retropharyngeal lymph node involvement. Zoumalan et al 14 and Randall et al 15 reported that cervical node necrosis visible on preoperative ct was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with head-and-neck squamous cell carcinoma, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% [16][17][18][19] . Those studies appear to suggest that snn might also be an unfavourable prognostic factor in patients with npc, and the results of the present study confirmed that suggestion.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported a strong correlation between ECS and necrosis with 95% sensitivity and 85% specificity. 15 A recent study by Joo et al, 21 which involved PET/CT for the identification of ECS, showed that fluorodeoxyglucose uptake could elevate sensitivity and specificity for the detection of ECS above those of contrastenhanced CT or MR imaging alone. The study showed that maximum standardized uptake values were significantly correlated with ECS (standardized uptake value detection cutoff, 2.25 on receiver operating characteristic curve demonstration; sensitivity and specificity, 85% and 88%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Zoumalan et al 15 found that lymph node necrosis was a good predictor of ECS. Classical imaging features of ECS include spiculated or irregular node borders, loss of the adjacent fat or muscle planes, and frank infiltration into structures adjacent to the lymph node.…”
mentioning
confidence: 99%